Are board characteristics relevant for banking efficiency? Evidence from the US. Issue 4 (1st August 2016) - Titova, Yulia
Abstract : Purpose: This paper aims to examine whether board-related characteristics matter for cost efficiency in banking sector. Design/methodology/approach: This study uses a sample of publicly traded US commercial banks and savings institutions to estimate a relationship between cost efficiency measured by stochastic frontier analysis and a set of board-related characteristics for the period 2007-2013. Findings: An inverted U-shape relation is found between board size and efficiency. Thus, there is a trade-off between costs and benefits of larger boards. Optimal board size is higher for banks with more complex operations. This study also observed an inverted U-shape relation between board independence and cost efficiency. The banks where the Chairman also executes the CEO responsibility show lower efficiency. However, a higher proportion of independent board members in banks with unitary leadership structure may mitigate the conflict of interest and lower efficiency stemming from CEO duality. Research limitations/implications: This study's evidence supports the Basel Committee on Banking Supervision emphasis on advising a board composition that provides for a sufficient degree of director independence. Practical Implications: The results are relevant for banks and their external and internal stakeholders. Banks may adjust their current board characteristics to increase the board effectiveness. Externally, potential investors can evaluate the quality of corporate governance of banks before making investment decisions. The empirical findings can also be useful for regulators imposing corporate governance codes in banking. Originality/value: To the best of the authors' knowledge, this is the first paper to provide empirical evidence on the impact of board characteristics on bank efficiency for a wide panel of US banks. Additionally, a comprehensive set of board-related variables is used.